2016
DOI: 10.1111/soin.12122
|View full text |Cite
|
Sign up to set email alerts
|

Doing Gender, Doing Surveys? Women's Gatekeeping and Men's Non‐Participation in Multi‐Actor Reproductive Surveys

Abstract: Gender differences in research participation have been documented in both quantitative and qualitative studies, a pattern that is particularly pronounced in studies of reproduction. We use the National Survey of Fertility Barriers to analyze three reasons frequently used to explain men's non-participation in reproductive research: (1) Reproduction is a sensitive subject for men, (2) reproduction is women's domain, and (3) men's unavailability due to seemingly pragmatic reasons (e.g., work schedule). Using bina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 54 publications
7
51
0
Order By: Relevance
“…The Mäori population does have a higher proportion of women compared to men (51% vs 49%, respectively; Statistics New Zealand, 2018); however, that alone does not account for the MIFAS gender skew. Gender has been found to have a considerable influence on survey participation internationally (Slauson-Blevins & Johnson, 2016;W. G. Smith, 2008); therefore, the gender difference in the MIFAS is not surprising and is consistent with patterns of survey responses found elsewhere.…”
Section: Gendersupporting
confidence: 63%
“…The Mäori population does have a higher proportion of women compared to men (51% vs 49%, respectively; Statistics New Zealand, 2018); however, that alone does not account for the MIFAS gender skew. Gender has been found to have a considerable influence on survey participation internationally (Slauson-Blevins & Johnson, 2016;W. G. Smith, 2008); therefore, the gender difference in the MIFAS is not surprising and is consistent with patterns of survey responses found elsewhere.…”
Section: Gendersupporting
confidence: 63%
“…The Māori population does have a higher proportion of women than men (51% vs 49% respectively; Statistics New Zealand 2018); however, that alone does not account for the MIFAS gender skew. Gender has been found to have a considerable influence on survey participation internationally, and women are typically much more likely to complete surveys than men (Smith 2008;Slauson-Blevins and Johnson 2016). Therefore, the gender difference in the MIFAS is not surprising and is consistent with patterns of survey responses found elsewhere.…”
Section: Gendermentioning
confidence: 58%
“…When asked why they participated in the study, 16 of the 25 participants reflected that 'interest' was one of their motivating factors. This included interest in the topic generally or specifically in relation to them as it was something they were considering at that time: Other researchers have identified interest as a motivating factor for research participation more generally (Clark, 2010) and have identified salience of topic as a factor which positively correlates with men's participation in reproduction research (Harrison, 2012;Slauson-Blevins and Johnson, 2016). The length of interviews (see above) and the fact that men talked a great deal and there were few silences also indicate that this was a topic of great interest to men.…”
Section: Interestmentioning
confidence: 99%